Designing model for adaptive variable withdrawal rate strategies to control misaligned grains during directional solidification of large-sized complex-shaped turbine blades - Yang Liu; Fu Wang; Jing Wang; Qiang Yang; Dichen Li; Jiantao Wu (Journal of Materials Research and Technology)
Misaligned grains present significant challenges in the directional solidification of complex-shaped industrial gas turbine (IGTs) blades made from Ni-based superalloys using the Bridgman method. These defects are closely associated with the bending of the solid/liquid (S/L) interface isotherm, a phenomenon heavily influenced by its relative position to the insulation baffle during solidification. The location of this isotherm is determined by the withdrawal rate employed. This study develops a simplified mathematical model that integrates blade and mold geometries, processing parameters affecting heat transfer, and the morphology of the liquidus isotherm. The model aims to design adaptive strategies for varying the withdrawal rate to control misaligned grain formation during directional solidification. By leveraging this theoretical framework, optimal adaptive withdrawal rate strategies were automatically generated, effectively flattening the liquidus isotherm and controlling misaligned grain formation in both dummy and actual IGT blades. This model, tailored to automatically design adaptive withdrawal rate routes, offers a robust strategy for producing misaligned-grain-free IGT blades.